The Role of Economic Literacy in Improving Student’s Critical Thingking Ability in the 21st Century (Lembaga Pengembangan Kinerja Dosen, 2022)
Students must understand economics in order to have adequate economic literacy. Students can use economics as a guide to find out markets, prices, and the type of business required for entrepreneurship. In critical thinking involves self-evaluation which results in analysis, evaluation, and explanation with conclusions based on evidence, concepts, methods, criteria, or contextual considerations. This study aims to analyze the influence of economic literacy in improving students' critical thinking skills in the 21st century. The method used in this research is in the form of literature study method, namely by using previous literature related to the research topic. The results of the study show that to produce competent individuals who are able to understand, involve, utilize, analyze and transform existing information, literacy must become a culture that is instilled from an early age. To be able to compete with the outside world and improve literacy skills, students must create a literacy culture that is instilled from an early age to produce competent human beings who are able to understand, involve, use, analyze and transform existing information.